The Comparison of Knee Joint Muscles Flexibility between Women with and without Radiographic Knee Osteoarthritis - Hedieh Moallem; Amir Hossein Barati; Elham Shirzad Araghi; Anoshirvan Kazemnejad (Shiraz University of Medical Sciences, 2020)
Background: Approximately 60% of individuals above 50 years of age are aﬀected by knee osteoarthritis (KOA). KOA is most commonly assessed through radiographic evaluation and classified using the Kellgren -Lawrence (KL) grading system with KL Grade 0 (KLG0) indicating a definite absence of radiographic KOA (RKOA) and KLG2 presenting a definite presence of RKOA. The current study compared knee joint muscle flexibility among three groups with KLG0, KLG2, and KLG3 RKOA. Methods: In this descriptive cross-sectional study, 94 KLG0, KLG2, and KLG3 knees on 57 women aged ≥40 years were examined. The flexibility of the quadriceps, hamstring, iliotibial band, adductor, and gastrocnemius muscles was compared. Results: Iliotibial band flexibility was lower in subjects with KLG3 RKOA than those with KLG2 (p <0.05) or KLG0 (p ≤0.001) RKOA, with the latter two groups being statistically equivalent (p =0.075). In addition, quadriceps muscle flexibility was lower in subjects with KLG3 RKOA than those with KLG2 (p ≤0.001) or KLG0 (p ≤0.001) RKOA, with the latter two groups being statistically different (p ≤0.001). No signiﬁcant diﬀerences were found between groups regarding other muscles (p >0.05). Conclusion: In patients with RKOA, the flexibility of the iliotibial band and quadriceps muscles may decrease as the disease progresses from KLG2 to KLG3. Moreover, quadriceps and iliotibial band flexibility may be lower in KLG3 compared to KLG0, with a lower likelihood of quadriceps flexibility in KLG2 compared to KLG0. These results suggest that quadriceps and iliotibial band stretching may be potentially important components of treatment.